Validity of Dementia Care Mapping on a neuro-rehabilitation ward: Q-methodology with staff and patients. (September 2013) - Westbrook, Jenna L.; McIntosh, Catriona J.; Sheldrick, Russell; Surr, Claire; Hare, Dougal J.
Abstract Background: Measuring the quality of care for people using neuro-rehabilitation services is a complex area requiring reliable methods that account for variable communication abilities/cognitive functioning. Dementia Care Mapping (DCM) is an observational method widely used in dementia care to improve person-centred care, which may be usefully applied to neuro-rehabilitation settings. Evaluation is vital to determine the tool's acceptability in this setting. Purpose: To explore the views of staff/patients regarding whether the use of DCM is acceptable in a neuro-rehabilitation setting. Method: DCM was conducted on an acute neuro-rehabilitation ward. Q-methodology, a technique for extracting subjective opinions, was used with 23 staff and 10 patients on the ward to evaluate the acceptability of DCM. Results: Factor analysis was performed separately for staff and patient Q-sorts. Each found a "consensus" factor where all participants indicated positive acceptability for the use of DCM. Further exploratory factors indicated that some staff/patients had additional views/concerns that were not captured by the first consensus factor. Conclusions: The results from this preliminary study are promising and indicate that DCM is potentially an acceptable tool to use in acute neuro-rehabilitation. Further research is needed to explore the acceptability of this tool more widely across neuro-rehabilitation settings. Implications for Rehabilitation Person-centred care is widely acknowledged as being important in all care settings, including neurorehabilitation. Dementia Care Mapping was deemed to be an acceptable approach for improving the quality of person-centred care on the basis of the views of staff and patients in a neurorehabilitation ward. Dementia Care Mapping, with adaptations for neurorehabilitation settings, successfully provides an acceptable framework for measuring and improving the quality of person-centred care in this setting.